(3HZjI GdShd ajeG hQO aj Gdbhds - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJI HZjI GdShd ajeG hQO ai Gdbhd s
(3BNQgG (B:s
(3hGdbQjI ai GddZI hGdLhUdI hGSfGgG LeGYI efbhWI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
Keywords: (3GdMOjK h GdeUWdMs